2011
DOI: 10.4137/pmc.s6803
|View full text |Cite
|
Sign up to set email alerts
|

Low Molecular Weight Opioid Peptide Esters Could be Developed as a New Class of Analgesics

Abstract: Low molecular weight opioid peptide esters (OPE) could become a class of analgesics with different side effect profiles than current opiates. OPE may have sufficient plasma stability to cross the blood brain barrier (BBB), undergo ester hydrolysis and produce analgesia. OPE of dipeptides, tyr-pro and tyr-gly conjugated to ethanol have a structure similar to the anesthestic agent, etomidate. Based upon the analgesic activity of dipeptide opioids, Lipinski’s criteria, and permeability of select GABA esters to cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…It is worth noting that analogues 5 and 6 with additional replacement of the Tyr 1 residue by Dmt were more stable compared with the related analogues 1–4. These results confirmed that cyclization protects peptides against enzymatic digestion and enhances their bioavailability. ,, Importantly, the replacement of the Tyr residue in position 1 by unnatural amino acid Dmt led to an additional enzymatic enhancement.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…It is worth noting that analogues 5 and 6 with additional replacement of the Tyr 1 residue by Dmt were more stable compared with the related analogues 1–4. These results confirmed that cyclization protects peptides against enzymatic digestion and enhances their bioavailability. ,, Importantly, the replacement of the Tyr residue in position 1 by unnatural amino acid Dmt led to an additional enzymatic enhancement.…”
Section: Discussionsupporting
confidence: 64%
“…These results confirmed that cyclization protects peptides against enzymatic digestion and enhances their bioavailability. 23,33,41 Importantly, the replacement of the Tyr residue in position 1 by unnatural amino acid Dmt led to an additional enzymatic enhancement.…”
Section: ■ Discussionmentioning
confidence: 99%
“…This leads to a cytotoxic intracellular acidosis that, together with the trapping of lactate and the consequential repression of its pro-invasive actions outside the cells, may eventually lead to a overall growth inhibition of the tumor. [340] …”
Section: Glycolytic Effectors As Potential Targets In Cancer Therapymentioning
confidence: 99%
“…S13 ). Based on Lipinski`s Rule for the central nervous system drugs (RoCNS), TAM B revealed closely CNS drug-likeness properties i.e., molecular weight = 433.170 (MW < 400), LogP = 3.081 (CLogP ≤ 5), a number of H-bond acceptor = 9 (HBA ≤ 7) and a number of H-bond donor = 4 (HBD ≤ 5) 47 , 48 . However, the topological polar surface area (TPSA) of compound 1 was 141.610 Å 2 which was higher than 90 Å 2 as a cut-off for optimal CNS exposure 49 .…”
Section: Resultsmentioning
confidence: 99%